Requirements and Capabilities for Fielding Cryogenic DT-Containing Fill-Tube Targets for Direct-Drive Experiments on OMEGA. (3rd April 2018) - Harding, D. R.; Ulreich, J.; Wittman, M. D.; Chapman, R.; Taylor, C.; Taylor, R.; Redden, N. P.; Lambropoulos, J. C.; Gram, R. Q.; Bonino, M. J.; Turner, D. W.
Abstract: Improving the performance of direct-drive cryogenic targets at the Omega Laser Facility requires the development of a new cryogenic system to (1) field nonpermeable targets with a fill tube and (2) provide a clean environment around the target. This capability is to demonstrate that imploding a scaled-down version of the direct-drive ignition target for the National Ignition Facility (NIF) on the OMEGA laser will generate the hot-spot pressure that is needed for ignition; this will justify future cryogenic direct-drive experiments on the NIF cryogenic targets. The paper describes the target, the cryogenic equipment that is being constructed to achieve this goal, and the proposed target delivery process. Thermal calculations, fill tube–based target designs, and structural/vibrational analyses are provided to demonstrate the credibility of the design. This new design will include capabilities not available (or possible) with the existing OMEGA cryogenic system, with the emphasis being to preserve a pristinely clean environment around the target and to provide upgraded diagnostics to characterize both the ice layer and the target's surface. The conceptual design is complete and testing of prototypes and subcomponents is underway. The rationale and capabilities of the new design are discussed.